Obesity-induced lysine acetylation increases cardiac fatty acid oxidation and impairs insulin signalling. (25th June 2014) - Alrob, Osama Abo; Sankaralingam, Sowndramalingam; Ma, Cary; Wagg, Cory S.; Fillmore, Natasha; Jaswal, Jagdip S.; Sack, Michael N.; Lehner, Richard; Gupta, Mahesh P.; Michelakis, Evangelos D.; Padwal, Raj S.; Johnstone, David E.; et al.
Abstract: Aims: Lysine acetylation is a novel post-translational pathway that regulates the activities of enzymes involved in both fatty acid and glucose metabolism. We examined whether lysine acetylation controls heart glucose and fatty acid oxidation in high-fat diet (HFD) obese and SIRT3 knockout (KO) mice. Methods and results: C57BL/6 mice were placed on either a HFD (60% fat) or a low-fat diet (LFD; 4% fat) for 16 or 18 weeks. Cardiac fatty acid oxidation rates were significantly increased in HFD vs. LFD mice (845 ± 76 vs. 551 ± 87 nmol/g dry wt min, P < 0.05). Activities of the fatty acid oxidation enzymes, long-chain acyl-CoA dehydrogenase (LCAD), and β-hydroxyacyl-CoA dehydrogenase (β-HAD) were increased in hearts from HFD vs. LFD mice, and were associated with LCAD and β-HAD hyperacetylation. Cardiac protein hyperacetylation in HFD-fed mice was associated with a decrease in SIRT3 expression, while expression of the mitochondrial acetylase, general control of amino acid synthesis 5 (GCN5)-like 1 (GCN5L1), did not change. Interestingly, SIRT3 deletion in mice also led to an increase in cardiac fatty acid oxidation compared with wild-type (WT) mice (422 ± 29 vs. 291 ± 17 nmol/g dry wt min, P < 0.05). Cardiac lysine acetylation was increased in SIRT3 KO mice compared with WT mice, including increased acetylation and activity of LCAD and β-HAD. Although the HFD and SIRT3 deletion decreased glucose oxidation, pyruvate dehydrogenase acetylation was unaltered. However, the HFD did increase Akt acetylation, while decreasing its phosphorylation and activity. Conclusion: We conclude that increased cardiac fatty acid oxidation in response to high-fat feeding is controlled, in part, via the down-regulation of SIRT3 and concomitant increased acetylation of mitochondrial β-oxidation enzymes.